Statistical Analysis Of Anxiety Levels And Their Effect On EFL Learner Writing Skills In 5th Semester - Abdul Syahid; Luciana; Novia Fitrian; Tria Angela Kusumaningrum (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
Writing skills are an important component of English language learning, yet many students face anxiety that interferes with their writing performance. This study aims to determine the relationship between anxiety levels and writing skills, focusing on anxiety related to grammar and evaluation. The method used was descriptive quantitative, with data obtained through questionnaires completed by 14 university students. This study provides insight into how anxiety affects EFL (English as a Foreign Language) students' writing skills, as well as the implications for English language teaching. The results are expected to assist educators in designing more effective strategies to address students' anxiety and improve their writing skills. Thus, this study contributes to a deeper understanding of the dynamics between anxiety and writing skills among EFL (English as a Foreign Language) students.